Cotton industry’s strategic responses to side marketing of cotton by contract farmers in Zimbabwe - Nyamwanza, Tonderai; Mapetere, Denver; Mavhiki, Severino; Nyamwanza, Lilian; Tumai, Kelvin (Progressive Academic Publishing, 2016)
Contract farming has been heralded as the panacea to the ailing agricultural output in Africa in general and Zimbabwe in particular. Traditionally Zimbabwe cotton industry was dominated by one government owned buyer, but with trade liberalization other players came into the market increasing demand for cotton. The majority of producers have always been the rural small scale farmer whose major handicap has always been lack of resource intensity. The research involved cotton farmers and companies in Gokwe north in Zimbabwe. Fifty people were contacted in all and desk research on contract farming in the country and southern Africa was conducted. To complement the primary data, the research considered annual reports of cotton companies in Zimbabwe from the period 2009 to 2014.This model was adopted by the cotton industry in Zimbabwe but it has been marred by side marketing. In response to side marketing, the cotton industry has adopted several strategies including lobbying for legislation to help curb the problem, group lending and close supervision. These strategies had little impact on solving the problem of side marketing of marketing. With regard to legislation the major problem farming inputs should only be provided to loyal farmers with better incentives. In addition, should stop interfering in the marketing of cotton.